NCOG-15. PREGNANCY AND GLIOMA. (9th November 2020) - Rodriguez, Andrew; Ruff, Michael
Abstract: Improvements in treatments and prognosis in glioma patients has led patients the opportunity for pregnancy despite their diagnosis. In this retrospective case series of 13 patients evaluated at Mayo Clinic, we identified patients who were pregnant at or after glioma diagnosis from 1998-2019. Clinical information was obtained through the electronic medical record. Tumor grade, treatments, peripartum complications, and pediatric outcomes were analyzed. Median follow-up for pregnant patients was 13.5 years (range, 0-24). Of the 13 patients, 2 patients received temozolomide and radiation during pregnancy for glioblastoma and had no peripartum complications. Median survival time in these patients after further treatments was 23.5 months (range, 23.3-23.8). Two children from these pregnancies had no fetal malformations or pediatric developmental delays with median follow-up of 8.8 years (range, 4.7-12.8). Three patients received radiation during pregnancy for high grade gliomas and had no fetal malformations or peripartum complications. Eight patients had one or multiple pregnancies with median 2 (range, 1-3) children at or after diagnosis with 14 children total. Eleven of the 14 children had no fetal malformations or peripartum complications and were conceived without reproductive assistive technologies. Two children, who were identical twins, were born with a placental malformation but otherwise had normal pediatric development. One child was born pre-term and had long-term developmental delays.